2018
DOI: 10.1208/s12249-018-1021-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Carrageenan Aerogel Microparticles as a Potential Drug Carrier

Abstract: Carrageenan is an anionic polysaccharide offering many advantages to be used in drug delivery applications. These include availability, thermo-stability, low toxicity, and encapsulating properties. Combination of these properties with aerogel properties like large surface area and porosity make them an ideal candidate for drug adsorption and delivery applications. Emulsion-gelation technique was used to prepare carrageenan gel microparticles with supercritical CO for drying and loading purposes. Ibuprofen has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The major applications in the field of biomedicine are shown as a schematic layout in Figure 6 . CGs are applied in various pharmaceutical formulations, including tablets [ 106 , 108 ], suppositories [ 109 , 110 ], films [ 111 ], fast-dissolving inserts (FDIs) [ 63 ], beads [ 112 , 113 ], pellets [ 114 , 115 , 116 ], microparticles [ 117 , 118 , 119 ], nanoparticles [ 120 , 121 , 122 , 123 , 124 , 125 ], inhalable systems, injectables [ 126 ], and hydrogels [ 127 , 128 , 129 ]. In addition, recent studies have shown that CGs are promising candidates in tissue engineering, thanks to their similarity to native glycosaminoglycans [ 127 , 128 , 130 , 131 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major applications in the field of biomedicine are shown as a schematic layout in Figure 6 . CGs are applied in various pharmaceutical formulations, including tablets [ 106 , 108 ], suppositories [ 109 , 110 ], films [ 111 ], fast-dissolving inserts (FDIs) [ 63 ], beads [ 112 , 113 ], pellets [ 114 , 115 , 116 ], microparticles [ 117 , 118 , 119 ], nanoparticles [ 120 , 121 , 122 , 123 , 124 , 125 ], inhalable systems, injectables [ 126 ], and hydrogels [ 127 , 128 , 129 ]. In addition, recent studies have shown that CGs are promising candidates in tissue engineering, thanks to their similarity to native glycosaminoglycans [ 127 , 128 , 130 , 131 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
“…Ibuprofen was selected as a model drug and the formulation was prepared using the emulsion-gelation technique. The prepared CG aerogel microparticles showed significant potential for use as a drug carrier, as ibuprofen was successfully loaded in the amorphous form inside the prepared microparticles with a notable enhancement in the drug release profile [ 118 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
“…The biodegradable carrageenan aerogel-based microparticles had high specific surface area (ranging between 33 and 174 m 2 /g), and good pore volumes and sizes. Obaidat et al 89 reported a emulsion-gelation technique to prepare carrageenan aerogelbased microparticles, and the drug of Ibuprofen was successfully loaded in these porous microparticles. These aerogel-based microparticles displayed significantly enhanced drug release properties.…”
Section: Aerogel-based Biomaterials For Drug Deliverymentioning
confidence: 99%
“…Aerogel have been also fabricated from other biopolymers such as pectin [ 62 ], starch [ 63 ], carrageenan [ 64 ], agar [ 65 ], and xanthan [ 10 , 66 ]. Nešić et al fabricated environmentally friendly pectin-based aerogel using TiO 2 as an antibacterial agent.…”
Section: Biopolymer-based Aerogelsmentioning
confidence: 99%